2022
DOI: 10.1029/2021jc018065
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Seasonal Intrusion of Water Masses and Their Impact on Nutrients in the Beibu Gulf Using Dual Water Isotopes

Abstract: A new data set of seasonal stable water isotopes (δD and δ18O) and temperature‐salinity profiles was applied to improve our understanding of water mass distributions and their impact on the environment of the Beibu Gulf (BG). Our study revealed that the coastal current (CC), West‐Guangdong coastal current (WGCC), and South China Sea water (SCSW) were the three dominant water masses in the BG, and their influence was exhibited in seasonal variations. The CC was the dominant contributor to the BG water during su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 75 publications
(132 reference statements)
2
93
1
Order By: Relevance
“…Higher nutrient concentrations were also observed in the other coastal bays of Beibu Gulf during the rainy seasons (Lai et al, 2014;Lao et al, 2021a andLao et al, 2021c), which were mainly related to the heavy land-source discharge induced by the increasing runoff around the coastal Beibu Gulf (Lao et al, 2020;Lao et al, 2021a). Particularly in Qinzhou Bay, because there are several rivers, such as the Qin River, Maoling River and Dafeng River, that directly input a large amount of terrestrial contaminants into the bay (Chen et al, 2019a;Zhang et al, 2019;Lao et al, 2020;Lao et al, 2021c;Lao et al, 2022b;Lyu et al, 2022). However, heavier DIN pollution was found in Xi Bay.…”
Section: Characteristics Of Nutrients In XI Baymentioning
confidence: 99%
See 4 more Smart Citations
“…Higher nutrient concentrations were also observed in the other coastal bays of Beibu Gulf during the rainy seasons (Lai et al, 2014;Lao et al, 2021a andLao et al, 2021c), which were mainly related to the heavy land-source discharge induced by the increasing runoff around the coastal Beibu Gulf (Lao et al, 2020;Lao et al, 2021a). Particularly in Qinzhou Bay, because there are several rivers, such as the Qin River, Maoling River and Dafeng River, that directly input a large amount of terrestrial contaminants into the bay (Chen et al, 2019a;Zhang et al, 2019;Lao et al, 2020;Lao et al, 2021c;Lao et al, 2022b;Lyu et al, 2022). However, heavier DIN pollution was found in Xi Bay.…”
Section: Characteristics Of Nutrients In XI Baymentioning
confidence: 99%
“…In addition, soil N was another important source that contributed to the heavy nitrogen pollution in the bay. With the increase in rainfall in the rainy season, a large amount of soil N on the land can be washed away and enter the coastal bay with the river (Lao et al, 2022b). Previous studies suggested that the nitrate source from the soil N in a coastal bay with riverine input was significantly higher than that in a bay without riverine input during the same period (Chen et al, 2022;Lao et al, 2022b).…”
Section: Quantification Of Nitrate Sources In XI Baymentioning
confidence: 99%
See 3 more Smart Citations